Microbicides for the Treatment of Sexually Transmitted HIV Infections - Singh, Onkar (J Pharm (Cairo), 2014)
Approximately 34 million people were living with human immunodeficiency virus (HIV-1) at the end of 2011. From the last two decades, researchers are actively involved in the development of an effective HIV-1 treatment, but the results intended are still doubtful about the eradication of HIV. The HIV-1 virus has gone from being an “inherently untreatable” infectious agent to the one liable to be affected by a range of approved therapies. Candidate microbicides have been developed to target specific steps in the process of viral transmission. Microbicides are self-administered agents that can be applied to vaginal or rectal mucosal surfaces with the aim of preventing, or reducing, the transmission of sexually transmitted infections (STIs) including HIV-1. The development of efficient, widely available, and low-cost microbicides to prevent sexually transmitted HIV infections should be given high priority. In this review, we studied the various forms of microbicides, their mechanism of action, and their abundant approaches to control the transmission of sexually transmitted infections (STIs).